Security, Emotions and Radical Right Populism: Beyond a ‘Flaunting of the Low’? - Hamilton, Claire (The British journal of criminology, 2024)
The rise of exclusionary populism is widely regarded as one of the most significant phenomena in today’s political world. Despite this, the relationship between populism and security remains under-explored in the literature, including the affective power of populist security narratives. Against this background, this paper conducts a comparative analysis of radical right populist discourse in response to two recent shocking crimes in France and Ireland. The different expression given to security concerns in the two countries, such as a much less antagonistic ‘flaunting of the low’ in France, is suggestive of a more contingent and institutionally mediated relationship between security and populism than the existing literature would suggest.